2018
DOI: 10.3390/ma11112210
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Surface Preparation and Wettability Transition of Titanium Alloy with Micro/Nano Hierarchical Texture

Abstract: Microstructures are applied to various hydrophobic/hydrophilic surfaces due to the role of adjusting the surface wettability. In this paper, a 1064 nm pulsed picosecond laser was applied to prepare a micro/nano hierarchical structure on the surface of the titanium alloy (Ti-6Al-4V). The microstructures consist of dimple arrays with various diameters, depths, and areal densities. They are obtained by controlling the pulse energy and the number of pulses. The nanostructures are periodic ripples, which are define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Further research has shown that the presence of common atmosphere gases such as CO 2 , O 2, and N 2 is not the main reason causing the carbon concentration changes, instead, the absorption of organic compounds seems to have a more significant influence on the carbon concentration [ 52 , 53 ]. These further supported with other research works showing that immersion or store in organic rich media will accelerate the carbon absorption process as in [ 44 , 54 , 55 , 56 ]. It seems the organic contamination during the annealing process could be the most possible reason.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Further research has shown that the presence of common atmosphere gases such as CO 2 , O 2, and N 2 is not the main reason causing the carbon concentration changes, instead, the absorption of organic compounds seems to have a more significant influence on the carbon concentration [ 52 , 53 ]. These further supported with other research works showing that immersion or store in organic rich media will accelerate the carbon absorption process as in [ 44 , 54 , 55 , 56 ]. It seems the organic contamination during the annealing process could be the most possible reason.…”
Section: Resultssupporting
confidence: 86%
“…The amount of silver decreased significantly due to the increase of oxygen and carbon species on the sample surface. The increased carbon concentration and associated nonpolar carbon group formation decreased the surface free energy [ 42 , 43 , 44 , 45 , 46 ]. Generally, the absorption of carbon item from the environment occurs in the long term [ 47 , 48 ], while the annealing process can accelerate the process in a short time [ 45 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…14(b). Yang et al [183] used a ps laser to create a hierarchical texture on a titanium alloy consisting of nano ripples superimposed on microdimple arrays that display superhydrophobic behavior. Materials with tailored wetting properties have potential applications in microfluidics, biomaterials, anti-icing, self-cleaning, etc.…”
Section: Laser Surface Texturing Methods and Diverse Patternedmentioning
confidence: 99%
“…Recently, superhydrophobic surfaces on titanium alloys with a water contact angle greater than 150° and a sliding angle lower than 10° have aroused much attention. They can provide widespread utilizations in anti-icing, anti-adhesion, and oil/water separation [ 3 , 4 , 5 ]. Although superhydrophobic surfaces have been proved to be effective in improving the corrosion resistance of titanium alloys, their low hardness, poor wear resistance, and high friction coefficient prevent them from being extensively employed in engineering applications [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%